The ape that understood the universe how the mind and culture evolve - Stewart-Williams, Steve 1971- (Cambridge University Press, 2018)
The Ape that Understood the Universe is the story of the strangest animal in the world: the human animal. It opens with a question: How would an alien scientist view our species? What would it make of our sex differences, our sexual behavior, our child-rearing patterns, our moral codes, our religions, our languages, and science? The book tackles these issues by drawing on ideas from two major schools of thought: evolutionary psychology and cultural evolutionary theory. The guiding assumption is that humans are animals, and that like all animals, we evolved to pass on our genes. At some point, however, we also evolved the capacity for culture - and from that moment, culture began evolving in its own right. This transformed us from a mere ape into an ape capable of reshaping the planet, travelling to other worlds, and understanding the vast universe of which we're but a tiny, fleeting fragment.